Comparative Study of Different Coil Geometries for Wireless Power Transfer Using Finite Element Method - Abdul Somad, Aiman (Universiti Teknologi PETRONAS, 2016)
Basic principles of inductive coupling of power transfer is based on the mutual inductance and coupling coefficient. This mechanism consists of the primary coil which is the transmitter and the secondary coil which is the receiver. This two coils will create the system of magnetic coupled inductors which generate the magnetic field and induces voltage to the receiver through an air gap. The larger the air gap will affected the performance of mutual inductance and coupling coefficient between inductors. The coupling coefficient is the current in one coil that link to the secondary coil which is the receiver with the fraction of the magnetic flux usually denoted by (k). Mutual inductance is when the current at the receiver is changing due to its mutual electromagnetic field. In addition, consideration of coil geometries also need to be taken for calculating the mutual inductance. In this project, the coupling coefficient between two coaxial coils will be analyse based on the air gap between the two coupling coils using finite element analysis.